Prevalence of Denture Stomatitis and Its Predisposing Conditions - A Retrospective Institutional study - J, GODLIN JENETA; R, SUBHASHREE.; M.S, NIVEDHITHA (The journal of contemporary issues in business and government, 2021)
Denture stomatitis is an inflammatory condition affecting denture wearers. It can occur mostly due to Candida infection or mechanical irritation from denture or allergic reaction to any of the material used for fabricating denture. Denture stomatitis is considered a multifactorial disease as it can occur due to occlusal disharmony and ill fitting dentures, blockage of mucous glands, candida albicans. Various treatment and preventive measures are based on etiology of denture stomatitis. The aim of this study was to investigate the prevalence of type of denture stomatitis and its association with age, gender and type of treatment given. A retrospective study was done from 1 June 2019 till 1 March 2020. Data was reviewed from the patients records and analysed the data of 86,000 patients between June 2019 and March 2020 that were documented in a private institution. Statistical analysis was performed to assess the association between denture stomatitis with age, gender and type of treatment given. Prevalence of Type I denture stomatitis was 35.19%, Type II denture stomatitis was 44.44%, Type III denture stomatitis was 20.37%. The association between age group and type of denture stomatitis showed that there was no significant relation between age and type of denture stomatitis. Association between type of denture stomatitis and gender was statistically significant (p<0.05). The association between the type of denture stomatitis and treatment given was not significant. Type II denture stomatitis is the most common type of denture stomatitis and occurs mostly between age groups 41 to 59 years with females having higher prevalence compared to males. Most common treatment suggested was denture correction. To reduce the risk of denture stomatitis, dentists should take a step to educate the patients how to use dentures and risk associated with not maintaining well and how to prevent it.